2015
DOI: 10.4236/jdm.2015.53021
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Clinical Features of Diabetic Foot in Cotonou

Abstract: This was a retrospective and descriptive study conducted from 1 July 2006 to 31 July 2011 and carried on 122 cases of diabetic foot collected a total of 706 diabetic patients hospitalized over a period of 5 years. Objective: To study the characteristics of diabetic feet in Cotonou. Results: The mean age of patients was 58.05 years ± 10.65 years, ranging from 35 years to 70 years. The sex ratio was 1.5. Duration of diabetes before the onset of diabetic foot was 11 years. The overall prevalence of diabetic foot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
1
0
0
1
Order By: Relevance
“…There is therefore a high rate of amputation, most often major, reported in African studies. Indeed, the amputation rate in our study was 38.16% and Kérékou A. et al [12] had found in the same service in 2015 a similar amputation rate of 32%. Moreover, Djibril et al [9] recently reported an amputation rate of 51.61% in their work in Togo.…”
Section: Discussionsupporting
confidence: 80%
“…There is therefore a high rate of amputation, most often major, reported in African studies. Indeed, the amputation rate in our study was 38.16% and Kérékou A. et al [12] had found in the same service in 2015 a similar amputation rate of 32%. Moreover, Djibril et al [9] recently reported an amputation rate of 51.61% in their work in Togo.…”
Section: Discussionsupporting
confidence: 80%
“…The male predominance among the population studied is a phenomenon confirmed by several authors. Kerekou found a sex ratio of 1.5 [9]; it was 2.5 for Amoussou-Guenou [10] and 2.46 for Sani [11] The majority of our patients were out of school (45%). This result is close to those of Traoré.…”
Section: Socio-demographic Characteristicsmentioning
confidence: 76%
“…5 Di Afrika sebesar 21,53% penderita DM menjalani perawatan di rumah sakit akibat masalah kaki diabetes, 95% diantaranya disebabkan masalah neuropati. 6 Penelitian di Indonesia pada tahun 2013, menunjukkan prevalensi pasien yang menjalani perawatan kaki diabetes adalah sebesar 25%. Walaupun tidak begitu banyak laporan riset terkait luka kaki diabetes di Indonesia.…”
unclassified